Pelatihan Penulisan Surat Dinas Untuk Siswa/i SMK 10 Nopember Jakarta - Utami, Diah; Youlia, Rikko Putra; Junaedi, Didi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
Official letter writing training for  students is an activity that aims to provide students with understanding and skills in writing official letters effectively and in accordance with applicable regulations. Official letters are a form of official communication in schools and other institutions, so it is important for students to understand how to write them well. Official letter writing training for students SMK aims to prepare them with the skills needed to communicate effectively in formal environments, both in the world of education and in the world of work. In this way, they are expected to be able to produce official letters that are clear, concise and in accordance with applicable standards.